Hemocytes from Pediculus humanus humanus are hosts for human bacterial pathogens - Coulaud, Pierre-Julien; Lepolard, Catherine; Bechah, Yassina; Berenger, Jean-Michel; Raoult, Didier; Ghigo, Eric (Frontiers in Cellular and Infection Microbiology, 2015)
Pediculus humanus humanus is an human ectoparasite which represents a serious public health threat because it is vector for pathogenic bacteria. It is important to understand and identify where bacteria reside in human body lice to define new strategies to counterstroke the capacity of vectorization of the bacterial pathogens by body lice. It is known that phagocytes from vertebrates can be hosts or reservoirs for several microbes. Therefore, we wondered if Pediculus humanus humanus phagocytes could hide pathogens. In this study, we characterized the phagocytes from Pediculus humanus humanus and evaluated their contribution as hosts for human pathogens such as Rickettsia prowazekii, Bartonella Quintana, and Acinetobacter baumannii.